Thermodynamic characteristics of methane adsorption on coals from China with selected metamorphism degrees: Considering the influence of temperature, moisture content, and in situ modification. (15th June 2023) - Zhang, Xiaoyu; Cai, Yongbo; Zhou, Tianbai; Cheng, Jian; Zhao, Guofei; Zhang, Liankun; Kang, Jianting
Highlights: The atomistic representations of the coal model containing both the pore structures and surface characteristics parameters were constructed. The methane adsorption isotherms and thermodynamic characteristics considering temperature and moisture contents were simulated and analyzed. In-situ modification have increased the pore volume by decomposition of minerals and functional groups on the coal surface, the graphitization process of coal is also promoted, which can accelerate the CBM extraction efficiency. Abstract: A better understanding of the thermodynamic characteristics of methane (CH4 ) adsorption on coal surfaces is needed for the high-efficiency coalbed methane (CBM) preextraction or prevention of coal and gas outbursts. In this study, atomistic representations of selected coal samples with different degrees of metamorphism, such as long flame coal, coking coal, and anthracite coal obtained from China were created; CH4 adsorption isotherms considering the temperature, moisture content, and microwave in situ modification for CBM preextraction were simulated and analysed. The coal molecular structural results showed that as the degree of coal metamorphism increased from long flame coal to coking coal and anthracite coal, the functional groups in the molecular structure of the coal reduced, while the degree of graphite increased. In situ modification of coal facilitated this process. The saturation adsorption capacity of CH4 decreased and then increased with increasing coal metamorphism degree and decreased linearly with increasing temperature. When water molecules were present, the adsorbed CH4 showed different degrees of decreasing trends with increasing moisture content. The isosteric heat of CH4 adsorption followed the order of coking coal > anthracite coal > long flame coal. The isosteric heat gradually decreased with increasing methane adsorption, and the presence of water molecules had a limited effect on the isosteric heat. In situ modification disrupted the self-conjugated hydrogen bonds, reduced the oxygen-containing functional groups, and decomposed some associated minerals in the coal samples. After in situ modification, the amount of methane adsorption decreased due to a greater contribution from the functional group change than that from the pore volume change, and the modification effect was more evident for the low-rank coal samples than for the middle and high metamorphism degree coal samples. In situ modification applied in the coal seams could contributed to designs for CBM exploration, and the results of this experiment and simulation could provide a novel theoretical basis for in situ modification technology.